The Mediating Role of Focus Level in the Relationship Between Abdominal Strength, Anaerobic Endurance, and Bowling Accuracy in Cricket Athletes - Zhafran, Muh. Dany; Syahruddin, Syahruddin; Mappanyukki, Andi Attsam (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2026)
This study aims to examine the role of focus level as a mediator in the relationship between abdominal muscle strength and anaerobic endurance on bowling accuracy among cricket athletes. Employing a quantitative approach with a path analysis design, the research involved 42 active male university-level cricket athletes at Universitas Negeri Makassar. Abdominal muscle strength was measured using a 1-minute sit-up test, anaerobic endurance via the Running-based Anaerobic Sprint Test (RAST) specifically evaluating the fatigue index, focus level through a concentration grid test, and bowling accuracy using a target-based accuracy test. The path analysis was conducted in two stages. The first stage revealed that abdominal muscle strength (β = .501, t = 5.780, p < .001) and anaerobic endurance (β = .497, t = 5.729, p < .001) were significant predictors of focus level, accounting for 88.3% of its variance (R2 = .883). In the second stage, focus level emerged as the most dominant predictor of bowling accuracy (β = .647, t = 6.163, p < .001). Crucially, the model confirmed significant indirect effects of abdominal muscle strength (β = .324, 95% CI [.214, .434] and anaerobic endurance (β = .322, 95% CI [.210, .434]) on bowling accuracy through focus level, with the overall model explaining 95.1% of the total variance (R2 = .951). While these substantial predictive values are contextually attributed to the specialized training phase and high homogeneity of the participants, caution should be exercised regarding external validation due to the relatively small and localized sample. The findings underscore that focus level acts as a potent partial mediator that translates physical capacity into technical precision, suggesting that cricket training programs should prioritize cognitive-attentional drills alongside physical development.